THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO AND EARNING PER SHARE ON STOCK PRICE - Kendrik Kendrik; Aldi Mukti; Verent Verent; Hendriyo Hendriyo; Billy Wiyogo; Jamaluddin Jamaluddin (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
The purpose of this research is to determine the Current Ratio, Debt to Equity Ratio, Earning Per Share has an effect on the Stock Price of the Sub Sector Property and Real Estate on the Indonesian Stock Exchange partially or simultaneously. This type of research was quantitative research. The data used in this research are secondary in the form of financial statements from the 2015-2018 period. The research method used in this research was the purposive sampling method and the sample used was 32 companies in the research period for 4 years, so that 128 sample data were obtained. The method used is multiple linear regression analysis using the help of Microsoft Excel 2010 and SPSS (Statistical Package for Social Sciences) version 23.0 with the stepwise method. The results of this research are: (a) Current Ratio partially has no effect on Stock Price, (b) Debt to Equity Ratio partially has no effect on Stock Price, (c) Earning Per Share partially has an effect on Stock Price, (d) Current Ratio, Debt to Equity Ratio and Earning Per Share simultaneously effect on Stock Price.